(untitled) (Statistics, Optimization & Information Computing, 2025)
A new extension of the inverse Weibull model is introduced and studied. Some of its statistical properties are derived. Di¤erent estimation methods are used for estimating the unknown parameter. We assessed the performance of all methods via simulation study. Two real data applications are used for comparing competitive estimation methods. The importance of the new model is demonstrated via two real data applications. The new model is much better than other competitive models in modeling the two real data sets.